Oral peptide delivery by tetraether lipid liposomes - Parmentier, Johannes; Thewes, Bernhard; Gropp, Felix; Fricker, Gert (International journal of pharmaceutics, 2011)
The aim of this study is to improve of oral peptide delivery by a novel type of liposomes containing tetraether lipids (TELs) derived from archaea bacteria. Liposomes were used for the oral delivery of the somatostatin analogue octreotide. TELs were extracted from Sulfolobus acidocaldarius and subsequently purified to single compounds. Liposomes were prepared by the film method followed by extrusion. Vesicles in size between 130 and 207 nm were obtained as confirmed by photon correlation spectroscopy. The pharmacokinetics of radiolabeled TELs in liposomes was investigated after oral administration to rats. 1.6% of the applied radioactivity in fed and 1.5% in fasted rats was recovered in the blood and inner organs after 2h, while most of the radioactivity remained in the gastro-intestinal tract. After 24h the percentage of radioactivity in inner organs was reduced to 0.6% in fed rats, respectively 1.0% in fasted animals. Several liposomal formulations containing dipalmitoyl phosphatidylcholine (DPPC) and TELs in different ratios were loaded with octreotide and orally administered. Liposomes with 25% TEL could improve the oral bioavailability of octreotide 4.1-fold and one formulation with a cationic TEL derivative 4.6-fold. TEL-liposomes probably act by protecting the peptide in the gastro-intestinal tract.
Gesehen am 21.09.2022